Application of Remote Sensing (RS) and Geographic Information System (GIS) in Erosion Risk Mapping: Case Study of Oluyole Catchment Area, Ibadan, Nigeria - , O. I. Ojo; , T. P. Abegunrin; , M. O. Lasisi (Archives of Current Research International, 2018)
Soil erosion is one of the major unresolved problems of rural agriculture. The causes of soil erosion in the study area are heavy precipitation, persistent drought, farming activities, deforestation and indiscriminate bush burning that expose soil to impact of rain drop. This study is aimed at applying Remote Sensing (RS) and Geographic Information System (GIS) in erosion risk mapping in Oluyole Catchment Area. Remote Sensing (RS) and Geographic Information System (GIS) techniques were used to map out the erosion risk areas. Google Earth and LANDSAT ETM+ were used to acquire the satellite imageries of Oluyole catchment area. Using high resolution imageries, a Digital Elevation Model (DEM) was developed with Surfer 8 and ArcGIS 10.0 to identify erosion risk areas. The Triangulated Irregular Network (TIN), flow length, flow accumulation and slope maps of the study area were generated with the use of Digital Elevation Model. The slope, flow accumulation and flow length maps were combined with land use map to produce erosion risk map with the use of map algebra in ArcGIS 10.0 software. The erosion risk map showed that the high, medium and low erosion risk areas covered 165 (26%), 269 (43%) and 195 km2 (31%) respectively while the land use map revealed that the areas occupied by vegetation, settlement and mixed are 221 (35%), 124 (20%) and 284 km2 (45%). Also, the Triangulated Irregular Network (TIN) indicated that the areas of high elevation are low in vulnerability to erosion, areas of medium elevation are moderately vulnerable to erosion as well as areas of low elevation are highly vulnerable to erosion accordingly. The results indicated that the used of remotely sensed data and GIS provide an effective approach to develop accurate in erosion risk mapping with a minimum amount of time, effort, and cost. This approach creates easily read and accessible charts and maps that facilitate the identification of erosion risk areas and also can be used effectively in public enlightenment, disaster response planning and erosion risk management.